2007
DOI: 10.1016/j.ejpain.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Neck flexor muscle fatigue in adolescents with headache – An electromyographic study

Abstract: This preliminary finding shows that increased neck flexor muscle fatigue in adolescents seems to be associated with tension-type headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
3
13
0
1
Order By: Relevance
“…In a population-based study, the quicker decline of MDF, indicative of greater muscle fatigue, was observed in sternocleidomastoid muscle of adolescents with TTH, during endurance test. This greater fatigability was explained by the conversion of muscle fiber types from slow to fast direction, due to neck flexor underuse, as one of the possibilities [11]. Similar results were obtained for women with TTH in masseter and sternocleidomastoid muscles during endurance tests [7].…”
Section: Morphological-based Measuressupporting
confidence: 73%
See 4 more Smart Citations
“…In a population-based study, the quicker decline of MDF, indicative of greater muscle fatigue, was observed in sternocleidomastoid muscle of adolescents with TTH, during endurance test. This greater fatigability was explained by the conversion of muscle fiber types from slow to fast direction, due to neck flexor underuse, as one of the possibilities [11]. Similar results were obtained for women with TTH in masseter and sternocleidomastoid muscles during endurance tests [7].…”
Section: Morphological-based Measuressupporting
confidence: 73%
“…Some headache studies show different power spectrum shape in patients vs. controls with employed mean (MNF) and median frequency (MDF) as solid indicators of such alternations [2,6,7,[10][11][12]. In a population-based study on adolescents, a quicker decline of MDF in TTH group compared with controls during neck flexion endurance test was found [11]. Consistent findings were also reported for women with TTH [7].…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations